Planning And Preparation Facing A Recession In 2023 - Rangga Munggaran; Rani Ligar Fitriani (EKOBIMA, 2023)
The Covid-19 pandemic period has led to prolonged challenges across various sectors, including the economy, resulting in an economic recession and its consequences. The post-pandemic inflation has risen to 6%, while the benchmark interest rate set by Bank Indonesia has increased. The concern about a global recession in 2023 due to high inflation, a substantial rise in interest rates, and geopolitical tensions has also surfaced, impacting the global economy.These developments have triggered economic issues like the depreciation of the rupiah, global economic weakening, decreased marginal efficiency of capital, high unemployment rates, reduced exports and investments, and a decline in tax revenues for the government. The government has even revised down its economic growth target, resembling a recession.The research follows a descriptive quantitative approach involving observational data collection methods, including field reviews and direct observations, data collection, information gathering, and scrutiny of existing records and documents.